PEMANFAATAN HASIL HUTAN BUKAN KAYU (HHBK) BAMBU OLEH MASYARAKAT TERASING (SUKU LAUJE)DI DESA ANGGASAN KECAMATAN DONDO KABUPATEN TOLITOLI - Muh Tang; Adam Malik; Abdul Hapid (Jurnal Warta Rimba, 2019)
Indonesia is a country that is blessed by God with a wealth of natural resources that supports the lives of its people, ranging from marine wealth to innumerable forest resources. The only problem that arises is the resource management of the wealth to be something useful. The purpose of this study was to determine the utilization of non-bamboo forest products made by the Lauje tribe in the Anggasan Village, Dondo District, Tolitoli Regency. This research was conducted in Anggasan Village, Dondo District, Tolitoli Regency, Central Sulawesi Province, for 3 months starting from March to May 2016. The method used in this research was the method of extracting information from the results of questionnaires and respondents so that it was hoped that this research could develop an object or real conditions in the field. The results of the study of the utilization of non-wood forest products (NTFPs) of bamboo by the isolated community (Lauje tribe) in Anggasan Village, Dondo District, ToliToli Regency are as handicrafts in the form of Patapi / sisiru (tatapi), hats (songko), chopsticks (chopsticks), aya (pagero) ), as a Nampang / place of water in the form of a place of water (sasauang) and a long place of water (bandal) and as materials / ingredients for building houses in the form of a house wall (bombonge), the floor of a house (basal) and a chicken coop (saloko). Utilization of bamboo by the community isolated Lauje tribe in Anggasan Village, Dondo District, Tolitoli Regency, is categorized as medium.Keywords: Non-Timber Forest Products, Lauje Tribe, Anggasan Village, Tolitoli Regency